Sweet cherry forms obtained with embryo culture techniques and their study in the Crimean steppe - L. A. Chernenkiy; L. A. Lukicheva (Труды по прикладной ботанике, генетике и селекции)
Background. Sweet cherry plants bear fruit annually, are high-yielding, and generate good profits. Cultivars with early-ripening fruits are specially valued. Cultivation of such sweet cherries makes it possible to extend the period of fresh fruit consumption and increase the profitability of orchards. It is therefore relevant to breed new early-ripening cultivars of this fruit plant.   Materials and methods. Twenty sweet cherry forms from five hybrid families obtained with in vitro embryo culture techniques at the Nikita Botanical Gardens were analyzed. The original early-ripening cultivars included in the hybridization of ‘Durona di Vignola 2’ and ‘Zemfira’ were used as a control. Flowering dates, fruit ripening dates, fruit weight and quality, resistance to negative temperatures (down to –25.6°C), and susceptibility to fungal diseases were studied from 2012 to 2021 at the Steppe Horticulture Laboratory, Nikita Botanical Gardens, using conventional methods.   Results and conclusions. Late-flowering breeding forms 460, 597, 602, 612 and 843 were selected for their lowest susceptibility to the effects of late spring frosts. Forms 343, 366, 453, 459, 460, 602, 612, 653, 353, 387, 600, 653 and 843 had early and very early fruit ripening periods. Forms 320, 434, 460, 593a, 597, 600, 601, 602 and 607 were identified for their high yields. Genotypes 459, 460, 601 and 843 demonstrated resistance to Cylindrosporium hiemale Higg., and 597, 843 and 320 to Monilia cinerea Bonord. High winter hardiness and frost resistance was observed in forms 355, 434, 459, 597 and 602. Breeding forms 460, 602 and 843 were identified as promising for a set of traits (late flowering, large high-quality fruits, resistance to major diseases, and high yield). They are of interest for introduction into horticultural production and use in further breeding work to develop new competitive cultivars.